1997
DOI: 10.1073/pnas.94.16.8848
|View full text |Cite
|
Sign up to set email alerts
|

Kinase domain of the muscle-specific receptor tyrosine kinase (MuSK) is sufficient for phosphorylation but not clustering of acetylcholine receptors: Required role for the MuSK ectodomain?

Abstract: Formation of the neuromuscular junction (NMJ) depends upon a nerve-derived protein, agrin, acting by means of a muscle-specific receptor tyrosine kinase, MuSK, as well as a required accessory receptor protein known as MASC. We report that MuSK does not merely play a structural role by demonstrating that MuSK kinase activity is required for inducing acetylcholine receptor (AChR) clustering. We also show that MuSK is necessary, and that MuSK kinase domain activation is sufficient, to mediate a key early event in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 41 publications
4
65
0
1
Order By: Relevance
“…We showed here that continuous stimulation by agrin is not necessary. In comparison to other receptor tyrosine kinases, MuSK is very unusual and its tasks are far more complex, as previously noted by others (19). MuSK not only triggers intracellular signaling but also has to localize such signaling to the correct site of a huge syncytial cell to achieve new protein synthesis as well as relocalization of dozens of preexisting proteins at the nascent postsynapse.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We showed here that continuous stimulation by agrin is not necessary. In comparison to other receptor tyrosine kinases, MuSK is very unusual and its tasks are far more complex, as previously noted by others (19). MuSK not only triggers intracellular signaling but also has to localize such signaling to the correct site of a huge syncytial cell to achieve new protein synthesis as well as relocalization of dozens of preexisting proteins at the nascent postsynapse.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, MuSK is required for presynaptic specialization of the nerve terminal (20). In line with such complex roles of MuSK, experiments with chimeric receptors have shown that, in contrast to growth factor receptors, MuSK's activated intracellular domain alone is not sufficient to reproduce MuSK's biological activity (i.e., AChR clustering)-structural portions of the MuSK extracellular domain are also important (19). Our data propose that even responses as complex as those initiated by MuSK, involving structural roles as well as catalytic tasks, may be triggered by a single brief pulse of ligand.…”
Section: Discussionmentioning
confidence: 95%
“…Because MuSK is clustered at synapses in rapsyn mutant mice ), these results suggest a model in which matrix-bound agrin engages and clusters MuSK, MuSK clusters an unknown linker protein(s), the linker protein(s) clusters rapsyn, and rapsyn clusters AChRs. This model, however, does not take into account the kinase activity of MuSK, which is required for agrin to stimulate clustering of AChRs Glass et al 1997). Moreover, because staurosporine inhibits AChR clustering without blocking agrinstimulated tyrosine phosphorylation of MuSK (Wallace 1994;Fuhrer et al 1997), there appears to be at least one kinase in addition to MuSK that is necessary for AChR clustering (Fig.…”
Section: Downstream Of Muskmentioning
confidence: 99%
“…Consistent with this expression pattern, we have found that ShcD can associate with muscle-specific kinase (MuSK), an RTK expressed at the skeletal neuromuscular junction (NMJ). On the postsynaptic muscle side of the NMJ, MuSK is stimulated by presynaptic motor neuron-derived agrin (53), which in turn leads to clustering and tyrosine phosphorylation of postsynaptic nicotinic acetylcholine receptors (AChRs) and remodeling of the neuromuscular synapse (10,11). Mice lacking either agrin or MuSK fail to develop normal neuromuscular synapses and consequently die at birth due to an inability to move or breathe (5,9).…”
mentioning
confidence: 99%